Development of a physiological model of human middle ear epithelium. Issue 5 (18th September 2021) - Mather, Michael William; Verdon, Bernard; Botting, Rachel Anne; Engelbert, Justin; Delpiano, Livia; Xu, Xin; Hatton, Catherine; Davey, Tracey; Lisgo, Steven; Yates, Philip; Dawe, Nicholas; Bingle, Colin D.; et al.
Abstract: Introduction: Otitis media is an umbrella term for middle ear inflammation; ranging from acute infection to chronic mucosal disease. It is a leading cause of antimicrobial therapy prescriptions and surgery in children. Despite this, treatments have changed little in over 50 years. Research has been limited by the lack of physiological models of middle ear epithelium. Methods: We develop a novel human middle ear epithelial culture using an air‐liquid interface (ALI) system; akin to the healthy ventilated middle ear in vivo. We validate this using immunohistochemistry, immunofluorescence, scanning and transmission electron microscopy, and membrane conductance studies. We also utilize this model to perform a pilot challenge of middle ear epithelial cells with SARS‐CoV‐2. Results: We demonstrate that human middle ear epithelial cells cultured at an ALI undergo mucociliary differentiation to produce diverse epithelial subtypes including basal (p63+), goblet (MUC5AC+, MUC5B+), and ciliated (FOXJ1+) cells. Mature ciliagenesis is visualized and tight junction formation is shown with electron microscopy, and confirmed by membrane conductance. Together, these demonstrate this model reflects the complex epithelial cell types which exist in vivo. Following SARS‐CoV‐2 challenge, human middle ear epithelium shows positive viral uptake, as measured by polymerase chain reaction and immunohistochemistry. Conclusion: We describe a novel physiological system to study the human middle ear. This can be utilized for translational research into middle ear diseases. We also demonstrate, for the first time under controlled conditions, that human middle ear epithelium is susceptible to SARS‐CoV‐2 infection, which has important clinical implications for safe otological surgery. Level of Evidence: NA.